Kearifan Lokal Dan Mitigasi Bencana Masyarakat Pantai Selatan Kabupaten Cilacap - Findayani, Aprillia; Utama, Nanda Julian; Anwar, Khoirul (Jurusan Sejarah Fakultas Ilmu Sosial Universitas Negeri Semarang, 2020)
This study aims to examine the local wisdom of the people of the southern coast of the Cilacap Regency to reduce disaster risk (DRR). This study used descriptive qualitative method. Data collection was carried out through observation, documentation, and interviews. Qualitative data analysis, through data reduction, data presentation, to concluding. The results showed that the people of Cilacap still firmly hold to their beliefs and customs reflected in their daily activities. This activity has been recorded historically for a long time The Cilacap community's local wisdom regarding earthquake and tsunami disaster mitigation is reflected in (1) Belief in the existence of Nyi Roro Kidul, who is the ruler of the South Coast who is believed to have experienced large waves. From here, the community learns about preparedness for tsunamis that can occur at any time. 2) Sedekah Laut, a ritual of making offerings into the sea as a symbol of gratitude for the blessings of the sea products and prayers and hopes for safety. (3) Mount Selok which considered to have a blessing for those who believe in it so that the community protects it as a tangible form of ecosystem preservation and a protective fence for the land from tsunamis.With these three local wisdoms, people from generation to generation have had the knowledge to be prepared, protect the environment, and be grateful for the blessings obtained from nature while maintaining its sustainability.